Data Visualization Analysis of Waste Production Volume in Every District of Tangerang Regency in 2021 Using Looker Studio and Big Query Platforms - Yanto, Budi; Sudaryanto, Aris; Hasri Ainun Pratiwi (Lembaga Penelitian dan Pengabdian Masyarakat, 2023)
The waste problem is a problem that continues to increase every year in Indonesia. Tangerang Regency as one of the regencies in Banten Province has the same problem related to the volume of waste production. Therefore, this study aims to analyze and visualize data on the volume of waste production in each sub-district in Tangerang Regency in 2021 using the Looker Studio and Big Query platforms. The method used in this research is descriptive method with a quantitative approach. The data used is secondary data obtained from the Tangerang Regency Environmental Service. The results showed that there were significant differences in the volume of waste production between one sub-district and another. Data visualization using the Looker Studio and Big Query platforms makes it easy to understand patterns and trends in the volume of waste production in each district. This research is expected to provide input for the Tangerang Regency government in making policies related to waste management in the area. This study employs data processing and analysis methods utilizing two platforms, namely Looker Studio and Big Query. The decision to adopt these platforms is backed by previous research, such as the study conducted by, which demonstrated that utilizing Looker Studio can lead to expedited and more effective business decision-making. Furthermore, the effectiveness of Big Query in processing large and intricate datasets has also been substantiated by various studies. By leveraging these platforms, the study aims to enhance the efficiency and accuracy of data processing and analysis for better-informed business decisions.